Implementation Completion Case Default Through Mechanism Lawsuit Simple: Decision Study Number : 4/ Rev.GS /2024/PN Gdt - Erlina B; M Cakra Bima (International Journal of Law and Society, 2025)
This study discusses the implementation of default case resolution through a simple lawsuit mechanism, referring to the case study of decision Number: 4/Pdt.G.S/2024/PN Gdt. Default or negligence in fulfilling obligations can cause disputes between the parties involved in the agreement. In Indonesia, one of the available alternative dispute resolutions is the simple lawsuit mechanism, which aims to provide convenience, efficiency, and accessibility for the public in claiming their rights legally. This study examines the process and procedures for resolving default disputes through simple lawsuits at the Gedong Tataan District Court, and analyzes how this mechanism can optimize justice and reduce the burden of cases in court.